Antihypertensive Property of Celery: A Narrative Review on Current Knowledge - Alobaidi, Sondos; Saleh, Eman (International Journal of Food Science, 2024)
Background. The incidence of hypertension is increasing significantly on a global scale, and it is considered the leading cause of heart disease and death. Despite the availability of hypotensive drugs, they have many side effects that decrease adherence to treatments and lead to uncontrolled blood pressure. Studies have revealed that celery contains bioactive compounds that oppose hypotensive effect. Methods. A thorough literature review was conducted using Scopus, PubMed, and Google Scholar databases. To identify relevant studies on the topic, our search strategy employed keywords such as “celery,” “Apium gravenols L,” “hypertension,” “high blood pressure,” “apigenin,” “antihypertensive,” and “hypotensive.” The search was limited to articles published between January 2013 and December 2023. The inclusion criteria were original research articles that involved both animal and human subjects, published in English, and reported results applicable to the subject of this review. Review articles or articles in the form of theses or books were excluded. Results. The available evidence revealed that celery enhances blood pressure parameters. Clinical trials clarified that celery possesses its effect through many bioactive compounds, specifically 3-n-butylphthalide and apigenin. Based on animal and human studies, celery seems to elicit blood pressure regulation mainly by the vasodilatory, diuretic, and calcium channel-blocking properties. Furthermore, celery seed extract seems to exert a bradycardia effect. Conclusion. The current literature review showed a considerable number of studies on the hypertensive models, which confirmed that celery and its extracts are effective hypotensive agents. Some limitations in comparing published data should be considered, including differences in doses, extracts, species of celery, and administration form.